Practice analysis among practitioners towards foot reflexology in Klang Valley, Malaysia - Nur Fatihah Nasmy (2021)
Practice analysis is a set of planned procedures used to classify the key elements of the job in the task performed or the nature of the worker which is required. The objective of practice analysis is to analyse a detailed description of the knowledge and ability required in an occupation that focuses on the demographic, professional characteristics, roles, responsibilities as well as the qualifications of practitioners in the reflexology centre. Every practitioner in the reflexology centre must ensure their reflexology treatment quality by involving in audit procedures so that they can evaluate and make an analysis of the practice in terms of management, assurance, and quality control. In Malaysia, practice analysis of practitioners illustrates the job responsibilities of people who work in the reflexology centre. However, at this professional level, lack of knowledge and skills in reflexology treatment such as communication skills, practitioners' attitudes towards the treatment, the procedure of treatment, and experiences affect the reflexology therapy. The aim of this study is to explore the practice analysis among practitioners towards foot reflexology in Klang Valley. The objectives are 1) to explore the practitioners’ knowledge of practice analysis towards foot reflexology in Klang Valley; 2) to explore the practitioners’ attitude of practice analysis towards foot reflexology in Klang Valley; and 3) to explore the implementation of practitioners’ safety process on practice analysis towards foot reflexology in Klang Valley. The data was collected through face-to-face, semi-structured interviews among six reflexology centres in Klang Valley. This study used purposive sampling and snowball sampling in six reflexology centres. The purpose sampling were the participants who are currently working as practitioners in foot reflexology centres and the snowball were the participants who were suggested from the earlier interview in the foot reflexology centres. The data gathered from the interviews were analysed using Thematic Analysis. The findings indicated that the practitioners’ knowledge towards foot reflexology is based on the participants' experiences and qualifications of more than three years in the field of reflexology treatment, and a certificate in reflexology where participants passed the examination techniques and practices. The result shows that the participants have explained the techniques used to approach a customer to undergo the foot reflexology treatment. However, not all participants can communicate with customers due to language barriers and the customers’ attitude or emotions at the time. This research indicated that ethical issues between practitioners and customers exist whereby most of the participants only care about customers’ satisfaction without focusing and understanding the ethics between practitioners and clients. The findings also show that the participants are practising the process of care in Good Practice Guidelines on reflexology for reflexologists practising in Malaysia. In conclusion, segregation of roles and responsibilities should be practised by practitioners who are engaged in reflexology treatment in Klang Valley